Pyrolysis of a perfluoro copolymer and its contribution to hydrogen fluoride (HF). (March 2020) - Zhao, Junchao; Fu, Yangyang; Lu, Song; Tao, Neng; Yin, Zhitao; Shahid, Muhammad Usman; Zhang, Heping
Abstract: Perfluoro copolymers (PFCPs) with PFD (long chain -(CF2 )7 CF3 moiety) have a wide range of applications, such as hydrophobic and oleophobic modification of dry chemicals suppressants. However, high fluorine contents may produce much HF in thermal environments. In this study, a newly designed perfluoro copolymer (DPFCP) was synthesized and its application, pyrolysis and HF production were investigated. The pyrolysis of DPFCP could be divided into three stages, whereas the gas mainly released at the second stage, including CH2 O, CO2, H2 O, Cx Hy, Cx Hy Fz, NH3, HF. A tube furnace was used to heating DPFCP to collect residual products and HF. The results indicated that HF was mainly produced under 370 °C. Graphical abstract: Image 1 Highlights: Designed perfluoro copolymer could modify APP powders to be oleophobic. The pyrolysis of designed perfluoro copolymer was divided into three stages. Gas release was mainly at second stage, including CH2 O, CO2, H2 0, Cx Hy, Cx Hy Fz, NH3, HF. DPFCP was likely to produce much HF when PFD removed from hydrocarbon chain. The whole pyrolysis process would produce 0.15% (wt) HF of DPFCP.